2011
DOI: 10.1021/ja205046h
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclopropanation with Gold(I) Carbenes by Retro-Buchner Reaction from Cycloheptatrienes

Abstract: Cationic gold(I) promotes the retro-Buchner reaction of 7-substituted 1,3,5-cycloheptatrienes, leading to gold(I) carbenes that cyclopropanate alkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

5
5

Authors

Journals

citations
Cited by 149 publications
(88 citation statements)
references
References 53 publications
2
84
0
2
Order By: Relevance
“…108 The retro-Buchner reaction of 7-substituted cycloheptatrienes 92 also generates gold( i ) carbenes (Scheme 29). 109 Cycloheptatrienes 92 react with gold( i ) through norcaradienes 93 to give gold( i ) carbenes 94 , which are trapped by alkenes leading to the corresponding cyclopropanes. A similar process was observed in the gas phase under electrospray ionization conditions.…”
Section: Evolution Of the Key Gold Intermediatesmentioning
confidence: 99%
“…108 The retro-Buchner reaction of 7-substituted cycloheptatrienes 92 also generates gold( i ) carbenes (Scheme 29). 109 Cycloheptatrienes 92 react with gold( i ) through norcaradienes 93 to give gold( i ) carbenes 94 , which are trapped by alkenes leading to the corresponding cyclopropanes. A similar process was observed in the gas phase under electrospray ionization conditions.…”
Section: Evolution Of the Key Gold Intermediatesmentioning
confidence: 99%
“…10,11 In contrast, we recently found that 7-substituted 1,3,5-cycloheptatrienes 1 react with cationic gold(I) complexes under catalytic conditions through their norcaradiene tautomers 2 to generate gold(I) carbenes [LAu=CHR] + ( 3 ) in an overall retro-Buchner process (a form of retro-cyclopropanation) (Scheme 1). 12 Our discovery of this reaction was prompted by the observation of a gold(I)-promoted retro-cyclopropanation in the context of a synthesis of 1,3-disubstituted naphthalenes. 13 The retro-Buchner reaction proceeds readily with 7-aryl- and 7-alkenyl-1,3,5-cycloheptatrienes, whereas 7-alkynyl-1,3,5-cycloheptatrienes react differently with gold(I) or gold(III) catalysts to form indenes by a complex cycloisomerization that proceeds through gold-stabilized barbaralyl cations.…”
Section: Introductionmentioning
confidence: 99%
“…The observed reactivity closely resembles that previously reported for the transition-metal-catalyzed decomposition of phenyldiazomethane [26] and the cyclopropanation of stilbenes by gold carbenes generated by retro-Buchner reaction (decarbenation). [27] Thep ossible reaction mechanisms leading to cyclopropanes and the kinetically unusual formation of ethylene were examined on am odel system by means of DFT calculations (Figure 3). Initially,apurely dissociative mechanism analogous to the proposed formation of carbenes from carbenoids of Pd [28] and Ni [29] was considered.…”
Section: Methodsmentioning
confidence: 99%